High α B-crystallin and p53 co-expression is associated with poor prognosis in ovarian cancer. Issue 6 (18th June 2019) - Tan, Lin; Sha, Ling; Hou, Ning; Zhang, Mei; Ma, Qian; Shi, Chuanbing
Abstract : Objectives: The present study investigated the correlation between α B-crystallin (CRYAB, HSPB5) and p53 expression in ovarian cancer and further analyzed the relationship between their expression and clinicopathology and the prognostic value of their co-expression in ovarian cancer. Methods: CRYAB and p53 expression was assessed using immunohistochemistry on ovarian cancer tumor tissues from 103 cases and validated in an independent group of 103 ovarian cancer patients. Results: High CRYAB and p53 expression rates in ovarian cancer tissues were 61.17% (63/103) and 57.28% (59/103), respectively, and their expression was positively correlated (r = 0.525, P =0.000). High CRYAB expression was significantly correlated with tumor size ( P =0.028), lymph node metastasis ( P =0.000), distant metastasis ( P =0.005), tumor node metastasis (TNM) stage ( P =0.002), and survival ( P =0.000), while high p53 expression was significantly correlated with tumor size ( P =0.006), pathological grade ( P =0.023), lymph node metastasis ( P =0.001), and survival ( P =0.000). Further studies found that the high CRYAB and p53 co-expression was also significantly correlated with pathological grade ( P =0.024), lymph node metastasis ( P =0.000), Distant metastasis ( P =0.015), TNM stage ( P =0.013), and survival ( P =0.000). High expression of either CRYAB or p53 and high co-expression of CRYAB and p53 were significantly correlated with poor disease-free survival (DFS) and overall survival (OS), respectively ( P <0.05). Patients with high CRYAB and p53 co-expression had the worst prognoses among the groups. In addition, multivariate Cox regression models showed that high expression of either CRYAB or p53 and high co-expression of CRYAB and p53 were independent prognostic factors for DFS and OS ( P <0.05). Moreover, the positive correlation and prognostic value of CRYAB and p53 expression were verified in another independent dataset. Conclusions: We demonstrated that patients with high CRYAB and p53 co-expression in ovarian cancer have significantly increased risks of recurrence, metastasis, and death compared with other patients. Therefore, more frequent follow-up of patients with high CRYAB and p53 co-expression is required. Our results also suggest that combination therapy with CRYAB inhibitors and p53 blockers may benefit future treatment of ovarian cancer patients with high co-expression of CRYAB and p53.